Thermo-microstructural-mechanical modeling on effect of travel speeds on thin Ti–6Al–4V deposits developed by laser wire deposition - Qi Zhang; Fatih Sikan; Nejib Chekir; Mathieu Brochu (Journal of Materials Research and Technology)
This study established a platform of three mechanistic models to understand the predictability of yield strength (YS) for Ti–6Al–4V deposits developed by laser wire deposition (LWD). Eight single-bead, multi-layer Ti–6Al–4V deposits were fabricated by LWD with four travel speeds for subsequent characterization and validation. A finite element analysis (FEA) thermal model was developed to simulate the deposition process and predict the thermal history. A microstructural model based on the α/β phase transformation kinetics was used to predict α/β phase fractions and α lath widths. The constitutive equations integrating the major strengthening mechanisms were used to predict the YS. The accuracy of all models was confirmed by comparison with experimental data. Grain size and tensile strength are statistically different only between the deposits produced with the slowest and fastest travel speeds. Microhardness is statistically similar across all travel speeds. Tensile results for all deposits are above the minimum tensile requirements according to the AMS4999 standard.